The contemplative soul : Hebrew poetry and philosophical theory in medieval Spain - Tanenbaum, Adena (Études sur le judaïsme médiéval, 2002)
During the eleventh and twelfth centuries, Jewish poets in Islamic Spain introduced philosophical themes into their devotional verse. Drawn to Neoplatonic thought, they made liberal use of its myth of the soul to explore the human relationship with the Divine. This novel merger reflected a conviction that ideas borrowed from Greco-Arabic philosophy meshed comfortably with traditional Jewish approaches to prayer and spirituality. This study focuses on Solomon Ibn Gabirol, Moses Ibn Ezra, Abraham Ibn Ezra, and Judah Halevi, polymath poets who also wrote philosophically-informed prose works. It probes the contemplative motifs in their religious verse, uncovering new and, at times, unorthodox layers of meaning. The book includes the Hebrew texts of representative poems accompanied by original English translations and detailed analyses.